Marine National Park Wandoor (A N Islands): a difficult but novel Management Challenge - Sinha, Pandey B. P.; Het, Ram; Saxena, Ajai (Indian Forester, 1991)
Management of Marine and Coastal Protected Areas is a comparatively new field as compared to the management of their counterparts i.e. terrestrial ecosystems. Due to various factors managing a marine/coastal area is a difficult preposition. This paper deals with the various unique features of marine/coastal protected areas. In general and discuss in detail about the management aspects, zonation and related problems; with respect to the Marine National Park, Wandoor.